Konstruksi Kurikulum Pendidikan Pemberdayaan Perempuan Lanjut Usia (Studi pada Posyandu Lansia Samara) - Sholichah, Aas Siti (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2023)
This paper aims to determine the curriculum and program of activities carried out by the Samara Elderly Posyandu in increasing the productivity of daily life. The research method used is a qualitative research method with a case study approach. For data collection using observation techniques, interviews and documentation. The Samara Elderly Posyandu (Sakinah, Mawadah and Rahmah) is one of the posyandu located in DKI Jakarta that focuses on assisting the elderly. To provide productivity values and fill old age activities, this posyandu develops a curriculum with a local curriculum approach that is tailored to the needs of the elderly, which is oriented to health, education and economic aspects. The program from the developed curriculum is the Healthy Elderly Program, which provides counseling about health and provides health services to the elderly. The next health program is elderly gymnastics. This elderly gymnastics activity is a means to nourish the body of the elderly, where the elderly are very physically sensitive. Programs related to education are learning the Koran and learning practical fiqh. Al-Quran learning starts from the basics and fiqh learning is related to prayer activities. This activity really helps the elderly spiritually in carrying out life in old age. Another program related to the economy is the waste bank. An activity related to the collection of used goods from paper, plastic, bottles and cans for further recycling. The waste bank is managed by and for the elderly. Those who can collect these items are exchanged for money which is then saved. Other activities are field trips or recreation. This activity is an entertainment activity for the elderly by visiting fun places. This activity is held twice a year